2020
DOI: 10.1093/molbev/msaa283
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity Contributes to Maize Adaptation and Heterosis

Abstract: Plant phenotypic plasticity describes altered phenotypic performance of an individual when grown in different environments. Exploring genetic architecture underlying plant plasticity variation may help mitigate the detrimental effects of a rapidly changing climate on agriculture, but little research has been done in this area to date. In the present study, we established a population of 976 maize F1 hybrids by crossing 488 diverse inbred lines with two elite testers. Genome-wide association study (GWAS) identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…This was supported by testing the interaction between the detected QTLs and the five sites, where 80.0% of the QTLs were found to be significantly interacting with the sites (Table S7; Materials and methods). This demonstrated the dynamic genetic effects of mean QTLs across sites and highlighted partial overlap for QTLs regulating mean and plasticity as reported in the previous studies 24,25,27 .…”
Section: Loci Associated With the Variation Of Remaining Traits-a Complex Genetic Architecture Involving Multiallelic Pleiotropy And Genosupporting
confidence: 79%
See 2 more Smart Citations
“…This was supported by testing the interaction between the detected QTLs and the five sites, where 80.0% of the QTLs were found to be significantly interacting with the sites (Table S7; Materials and methods). This demonstrated the dynamic genetic effects of mean QTLs across sites and highlighted partial overlap for QTLs regulating mean and plasticity as reported in the previous studies 24,25,27 .…”
Section: Loci Associated With the Variation Of Remaining Traits-a Complex Genetic Architecture Involving Multiallelic Pleiotropy And Genosupporting
confidence: 79%
“…Previous studies showed that the highly selected region during maize adaptation to temperate climate explained less G-by-E variation than the selected region 12 and the allele frequency of plasticity QTLs were changed between temperate and tropical lines 27 , suggesting that directional selection may have shaped their genetic diversity. Here, we explored whether the 93 plasticity QTLs were selected during intense artificial selection by evaluating their allele frequency changes using two collections of breeding materials, one collection from China that has predominantly been deployed in the 1960s, 1980s, and early 2000s, and a second collection from US before and after 2003 50 .…”
Section: Plasticity Qtl May Have Been Subjected To Directional Selection During the Breeding Programmentioning
confidence: 96%
See 1 more Smart Citation
“…The potential of phenotypic plasticity to evolve [ 61 ] in maize lines endowed with native resistance to FAW foliar damage due to the strong influence of genotype by environment (GXE) interaction underscores the importance of conducting multi-year germplasm evaluations when screening maize germplasm for resistance to FAW foliar damage. Previous studies have also concluded that the analysis of genotype by environment interactions could facilitate the identification of cultivars whose yield-stability are related to the linear effect of an environmental index [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A two-step approach has been widely used to study the genetics underlying hybrid performance, where the first step consists of estimating the GCA, SCA and the MPH ( Guo et al, 2014 ; Zhou et al, 2018 ; Yi et al, 2019 ) and the second step represents the QTL mapping step with the GCA, SCA and MPH treated as the traits of interest. In a previous genome-wide association study (GWAS) with an NCII population, different coding schemes for the genotypes were applied, namely the additive, dominance and recessive coding ( Hyun et al, 2008 ; Liu et al, 2021 ). However, the additive model was usually not sufficient to explain hybrid performance and MPH.…”
Section: Introductionmentioning
confidence: 99%